Molecular Modeling of An Analog Of Curcumin Compounds Pentagamavunon-0 (PGV-0) And Pentagamavunon-1 (PGV-1) Through Computational Chemistry Methods Ab-Initio HF/4-31G - Prakoso, Nurcahyo Iman; Hakim, Lukman; Hidayati, Nuri (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2017)
Breast cancer is the second largest number of cancer cases in Indonesia, after cervical cancer. The growth of these cancer cells can be prevented with compounds Pentagamavunon-0 (PGV-0) and Pentagamavunon-1 (PGV-1). This compound is an analog of curcumin compounds that have anti breast cancer activity. Modeling the structure of compound PGV-0 and PGV-1 through computational chemistry methods Ab-initio HF/4-31G could be used to predict the geometry and structure elucidation spectra associated with pharmacological activity such as anticancer compounds theoretically.This research involves modeling the structures and spectra prediction calculation compounds PGV-0 and PGV-1 by computational chemistry methods Ab-initio HF/4-31G, using Gaussian03W. The result using Ab-initio HF/4-31G method then compared with data from experimental geometry and the results of calculations with AM1.The results showed that computational chemistry methods Ab-initio HF/4-31G calculations give better results for modeling the structure compared semiempirik method AM1.